Measuring Human Resource Engagement in Information Security Practices in Technology-Based Business Contexts - Purnomo, Yudiyanto Joko (Technology and Society Perspectives (TACIT), 2024)
Many businesses are currently transitioning to digital models, relying on information technology to store, manage, and process critical information. However, with increased technology usage, threats to information security are also on the rise. This research aims to measure the engagement of human resources in information security practices in the context of technology-based businesses. The research method employed is a qualitative literature review aimed at investigating various perspectives, approaches, and findings related to human resource engagement in information security practices in technology-based business contexts. Data for this literature review were obtained through searching scholarly articles using the Google Scholar search engine, spanning from 2006 to 2023. The study findings indicate that in the continuously evolving digital era, human resource engagement in information security practices is crucial for the success and sustainability of technology-based businesses. This responsibility extends beyond the IT department and involves collective responsibility throughout the organization. Measuring this engagement requires a holistic approach involving management, operational levels, and corporate culture.